Keberlakuan dan Kekuatan Hukum Terhadap Wasiat yang Melanggar Legitieme Portie Ahli Waris - Astrid Athina Indradewi (SAPIENTIA ET VIRTUS, 2023)
This study aims to analyze the legal validity and legal force of a testament whose contents violate the 'legitieme portie' of the heirs. The testament may not contain provisions that reduce the absolute share of the heirs. The Civil Law Code stipulates a system of restrictions on the allocation of inheritance to be distributed to heirs through 'legitieme portie' in order to protect heirs from the tendency for heirs to benefit other people. This study uses a normative juridical research method with conceptual and statutory approaches. The results of this study are testaments that contain provisions regarding the distribution of inheritance which violates the 'legitieme portie' of heirs, thus legally it must be prosecuted and enforced based on the provisions of Article 913 juncto Article 914 juncto Article 920 of the Civil Law Code. However, if the heirs do not sue, the testament as intended will continue as it is. In other words, the testament remains valid even if it contains a violation of the 'legitieme portie' of the heir as long as it has not been canceled by the injured party.